Observation On Void Formed In Oxide Scale Of Fe-Cr-Ni Alloy At 1073k In Dry And Humid Environments - Kaderi, Akbar; Mohd Zainal, Ahmad Zaki; Ani, Mohd Hanafi; Othman, Raihan (IIUM Engineering Journal, 2012)
Void formation in oxide scale during high temperature oxidation is a common phenomenon. Over a long period of time voids will affect the mechanical property of scales by influencing the cracking and spalling. Voids formed in dry environment are different than that of formed in humid environment. With the presence of water vapor in humid environment the formation of void will increase, thus greater number of void compared to that in dry environment. Fe-Cr-Ni alloy samples were exposed isothermally at 1073 K in air (P_(O_2 )= 0.21atm = 2.1×?10?^(5 )Pa) and humid (air + steam) environments. XRD analysis done to all samples confirms that Fe2O3, Fe3O4, NiCr2O4, FeCr2O4, Cr2O3 and NiO phases exist in the scale. EDX analysis done shows varying compositions of Fe,Cr,Ni and O in outer and inner oxide scale, oxide scale/metal interface and metal. Field emission scanning electron microscope (FE-SEM) was used to investigate voids formed in the cross sections of the oxidized samples. Volume fraction of voids in the oxide scale was calculated in accordance to the cross sectional area fraction of voids in the scale. It shows that Fe-Cr-Ni alloy samples exposed in humid environment has as high as 71% more voids than that exposed in dry environment. It is concluded that the humid environment increased the number of void formed in the oxide scale, thus facilitates the exfoliation of protective scale during the high temperature oxidation. ABSTRAK: Pembentukan gelembung udara di dalam lapisan oksida ketika proses pengoksidaan di suhu tinggi merupakan satu fenomena biasa. Pada satu jangka masa yang panjang gelembung-gelembung ini akan memberi kesan kepada sifat mekanikal oksida dengan mempengaruhi pembentukan keretakan dan pengelupasan oksida. Gelembung udara yang terbentuk di dalam persekitaran kering berbeza daripada yang terbentuk di dalam persekitaran lembap. Dengan adanya wap air, pembentukan gelembung akan bertambah berbanding yang terbentuk di dalam persekitaran kering. Sampel aloi Fe-Cr-Ni telah dioksidakan secara isoterma pada suhu 1073 K di dalam udara (P_(O_2 )= 0.21atm = 2.1×?10?^(5 )Pa) dan lembap (udara + wap air). Analisis Pembelauan Sinar – X (XRD) kepada semua sampel menunjukkan oksida yang terbentuk ialah Fe2O3, Fe3O4, NiCr2O4, FeCr2O4, Cr2O3 dan NiO. Analisis Penyebaran Tenaga Sinar – X (EDX) menunjukkan komposisi Fe, Cr, Ni dan O yang berubah - ubah di lapisan oksida luar dan dalam, oksida/ antara muka logam dan logam. Mikroskop Imbasan Elektron-Pancaran Medan (FE-SEM) digunakan untuk meneliti gelembung di dalam oksida pada keratan rentas sampel. Pecahan isi padu gelembung yang terbentuk pada oksida dikira dengan merujuk kepada pecahan luas keratan rentas pada oksida tersebut. Sampel aloi Fe-Cr-Ni yang dioksidakan di dalam persekitaran lembap mempunyai kandungan gelembung udara 71% lebih banyak berbanding dengan yang dioksidakan di dalam persekitaran kering. Kesimpulannya persekitaran lembap meningkatkan bilangan gelembung yang terbentuk di dalam lapisan oksida, sekaligus memudahkan pengelupasan oksida semasa pengoksidaan suhu tinggi. KEYWORDS: high temperature oxidatio;, Fe-Cr-Ni alloy; void formation; quantitative analysis of voi;, dry environment; humid environment